493 Tired and hungry: a potential role for CD47 in T cell exhaustion. (9th November 2020) - Mangarin, Levi; Liu, Cailian; Zappasodi, Roberta; Holland, Pamela; Wolchok, Jedd; Merghoub, Taha; Weng, Chien-Huan; Weng, Chien-Huan; Schroder, David
Abstract : Background: Multiple suppressive mechanisms within the tumor microenvironment are capable of blunting anti-tumor T cell responses, including the engagement of inhibitory receptors expressed in tumor-associated, exhausted CD8+ T cells, such as programmed cell death protein 1 (PD-1), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), lymphocyte-activation gene 3 (LAG-3), 2B4 (also known as CD244), and T cell immunoreceptor with Ig and ITIM domains (TIGIT). 1 2 While immune checkpoint blockade therapies aimed at reinvigorating T cell effector function have demonstrated their clinical effectiveness, 3 4 not all patients demonstrate long-term disease control. 5 The refractory nature of terminally differentiated, exhausted CD8+ T cells to be reinvigorated by PD-1 blockade is one potential cause. 6–8 This limitation warrants the need to explore modulatory pathways that potentially program T cells toward exhaustion. Methods: Single cell-RNA sequencing (scRNA-seq) data derived from the tumor-infiltrating lymphocytes (TILs) of melanoma patients 9 were used for transcriptomic analysis and flow cytometry results were used to quantify protein levels in TILs. Murine B16-F10 (B16) melanoma model was used for both in vitro and in vivo studies. TCR-transgenic Pmel-1 and OT-1 transgenic mice, as well as CD47-/- (knockout, KO) mice were purchased from the Jackson Laboratory to generate CD47+/+ (wild-type, WT), CD47± (heterozygote, HET) mice with Pmel-1 or OT-1 background. For T cell co-transfer studies, Rag-deficient mice or C57BL/6j mice with sub-lethal irradiation (600cGy) were used as recipients. Naïve TCR-transgenic CD47-WT and CD47-HET CD8+ T cells were labelled, mixed in a 1:1 ratio for co-transfer experiments. Results: Flow cytometry analysis of human melanoma TILs found a strong upregulation of CD47 expression in tumor-associated, exhausted CD8+ T cells. We confirmed that CD47 transcription is significantly elevated among CD8+ T cells with a phenotype consistent with exhaustion using scRNA-seq results of TILs derived from melanoma patients. 9 Our study in murine B16 melanoma model confirms our finding in melanoma patients. To specifically address the role of CD47 in anti-tumor CD8 effector function, we conducted T cell co-transfer studies and found that CD8+ T cells with lower copy number of CD47 (CD47-HET) significantly outnumber the co-transferred CD47-WT CD8+ T cells within the tumor, exhibiting an enhanced effector function and less exhausted phenotype. Our study demonstrates a potentially novel role for CD47 in mediating CD8+ T cell exhaustion. Conclusions: CD47 expression in CD8+ T cells programs T cells toward exhaustion. Ethics Approval: All mice were maintained in microisolator cages and treated in accordance with the NIH and American Association of Laboratory Animal Care regulations. All mouse procedures and experiments for this study were approved by the MSKCC Institutional Animal Care and Use Committee (IACUC). References: Wherry EJ and M Kurachi. Molecular and cellular insights into T cell exhaustion. Nat Rev Immunol 2015;15(8): p. 486–99. Thommen DS and Schumacher TN. T Cell Dysfunction in Cancer. Cancer Cell 2018;33(4): p. 547–562. Ribas A and Wolchok JD. Cancer immunotherapy using checkpoint blockade. Science 2018. 359(6382): p. 1350–1355. Sharma P and Allison JP. The future of immune checkpoint therapy. Science 2015; 48(6230): p. 56–61. Sharma P, et al. Primary, adaptive, and acquired resistance to cancer immunotherapy. Cell 2017. 168(4): p. 707–723. Schietinger, A., et al., Tumor-specific T cell dysfunction is a dynamic antigen-driven differentiation program initiated early during tumorigenesis. Immunity 2016;45(2): p. 389–401. Pauken KE, et al., Epigenetic stability of exhausted T cells limits durability of reinvigoration by PD-1 blockade. Science 2016;354(6316): p. 1160–1165. Philip M, et al., Chromatin states define tumour-specific T cell dysfunction and reprogramming. Nature 2017;545(7655): p. 452–456. Sade-Feldman M, et al., Defining T Cell States associated with response to checkpoint immunotherapy in melanoma. Cell 2018;175(4): p. 998–1013e20.